American Atlantic ports-north sheet [Material cartográfico] - Philip, George; George Philip & Son Ltd.; Merchant, Shippers, Exported and Ocean Travelles; The London Geographical Institute (George Philip & Son, Ltd, 1922)
Inserta: Chicago Boston Harbour New York Harbour "Soo" canals Continuation of Lake Superior The coast from New York to Boston Buffalo; Montreal Halifax Newfoundland Copia digital. Madrid : Ministerio de Cultura. Dirección General del Libro, Archivos y Bibliotecas, 2010